MANAJEMEN KURIKULUM PENDIDIKAN KARAKTER BERBASIS NILAI-NILAI KEAGAMAAN - Ubaidillah, Aan Eko Khusni (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
Education requires good management including Islamic education. The main aspect of the success of national education is the curriculum. Therefore, good management (management / regulation) of a curriculum is a necessity in achieving educational goals. Curriculum management is a system of managing a curriculum that is cooperative, comprehensive, systemic, and systematic in order to realize the achievement of curriculum objectives. Character education should be carried out in planned and measurable stages and have a strong foundation, especially religious-based values